Economic analysis and perception of integrated wildlife / livestock farming as an alternative land use option in rural areas of Mopani District in Limpopo Province, South Africa - Cholo, Machuene Sharlyn (My University, 2017)
Wildlife farming has become an important land use alternative, especially in most developing countries where there is an abundance of wildlife resources. In South Africa, integrated wildlife/livestock was mostly practiced by commercial farmers on a privately owned land but in recent years, potential for income generation in the industry has grown. Smallholder farmers are increasingly being assisted to explore practicing integrated wildlife/livestock on communal land after receiving land through restitution programme. The aim of the study was to examine costs and benefits associated with integrating livestock with wildlife in a smallholder agricultural context. Structured questionnaires were used to collect data from 71 respondents situated in Ba-Phalaborwa Municipality selected using multistage random sampling technique. Cost-benefit approach and weighted decision matrix were used for economic analysis and also to identify potential trade-offs. Furthermore, the study used descriptive statistical analysis to identify opportunities and challenges faced by farmers. Some of the livestock costs identified include feeds, vaccines and labour costs. Benefits of wildlife include income from trophy hunting and selling meat from wild animals. Cost-Benefit Ratio (CBR) as a tool of cost benefit analysis techniques, was used in order get 0.67 in livestock farming, this shows that the project may not be sustainable whereas that of wildlife farming was 1.13 which indicate that the project will yield positive outcome for community involved. There are trade-offs that farmers will have to consider when shifting towards integrated wildlife/livestock such as reduced livestock benefits and increased wildlife benefits. Livestock diseases, stock theft and others are the identified challenges associated with integrated wildlife/livestock. Descriptive results indicated that 40% of livestock farmers mentioned that they are strongly affected by stock theft and disease transmission. The identified opportunities of integrated wildlife/livestock were business and job creation for rural households. Given the findings, the study therefore, recommends that government and private sector should assist farmers with training in wildlife farming so that they can be competitive in commercial wildlife farming. Funds should be made available for setting up infrastructure suited for wildlife land uses.
Thesis ( M. Sc.((Agricultural Economics)) -- University of Limpopo, 2017.
Keywords: Land use; Integrated livestock; Wildlife farming; Land use, Rural -- South Africa; Land reform beneficiaries -- South Africa; Livestock productivity -- South Africa.